2008
DOI: 10.1016/j.ergon.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration alters proprioception in the trunk

Abstract: Abstract:Occupational whole body vibration has long been associated with low back injuries.However, the mechanism of these injuries is not well understood. In this paper, the effect of whole body vibration on proprioception and dynamic stability was examined. Subjects exposed to 20 minutes of vertical, seated, whole body vibration were found to have a 1.58 fold increase in position sense errors after vibration relative to controls exposed to 20 minutes of the same seated posture without vibration exposure. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
8
1
4
Order By: Relevance
“…In the study by Slota et al (2008), spinal stability decreased following 30 min of WBV exposure on a wobble chair, as evidenced by changes in kinematic and stability assessment measures. This was similar to the findings of Li et al (2008) who, using 3D motion analysis, illustrated that position sense error, which measures the ability to reproduce a target posture (Li et al 2008), was significantly greater in vibration conditions compared to control conditions. It was concluded that WBV reduces the lumbar spines' sensory and neuromotor habituation properties (Carlsoo 1982;Desmedt 1983;Vermeersch et al 1986).…”
Section: Spinal Stability and Balance Responsessupporting
confidence: 89%
“…In the study by Slota et al (2008), spinal stability decreased following 30 min of WBV exposure on a wobble chair, as evidenced by changes in kinematic and stability assessment measures. This was similar to the findings of Li et al (2008) who, using 3D motion analysis, illustrated that position sense error, which measures the ability to reproduce a target posture (Li et al 2008), was significantly greater in vibration conditions compared to control conditions. It was concluded that WBV reduces the lumbar spines' sensory and neuromotor habituation properties (Carlsoo 1982;Desmedt 1983;Vermeersch et al 1986).…”
Section: Spinal Stability and Balance Responsessupporting
confidence: 89%
“…According to Gellerstedt (2002), 4,000 control inputs per hour have to be carried out by the operator, due to the lack of automatic functions of the boom and harvester head. Despite the ergonomic design of the cabs, the operators of mobile machinery are exposed mainly to noise (Hansson 1990;Axelsson 1998;Marsili et al 1998;Nieuwenhuis, Lyons 2002;Messingerová et al 2005;Sümer 2006;Beuk et al 2007;Gerasimov, Sokolov 2009;Aybek et al 2010;Bilski 2013), whole-body vibrations (Boileau, Rakheja 1990;Burdorf, Swuste 1993;Magnusson et al 1993;Hansson 1995;Huston et al 1999;Hinz et al 2002;Paddan, Griffin 2002;Hostens, Ramon 2003;Chen et al 2003;Sherwin et al 2004a,b;Deprez et al 2005;Kolich et al 2005;Tiemessen et al 2007;Li et al 2008;Gerasimov, Sokolov 2009), microclimatic conditions -mostly temperature, and airflow velocity inside the cab (Gao, Niu 2004;Kaynakli, Kilic 2005;Huang et al 2006;Mezrhab, Bouzidi 2006;Cengiz, Babalik 2007;Farzaneh, Tootoonchi 2008;Kim et al 2009;Zhang et al 2009a,b;Alahmer et al 2011), and severe mental and sensory load (Axelsson, Pontén 1990;Poschen 1993;…”
mentioning
confidence: 99%
“…For example, some pilots who mentioned lower back pain had worked as helicopter pilots, which has been shown to overload the lower back with vibration (20).…”
Section: Discussionmentioning
confidence: 99%